Blockchains, Real-Time Accounting and the Future of Credit Risk Modeling - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2016)
In this paper (letter) I discuss how blockchains potentially could affect the way credit risk is modeled, and how the improved trust and timing associated with blockchain-enabled real-time accounting could improve default prediction. To demonstrate the (quite substantial) effect the change would have on well-known credit risk measures, a simple case-study compares Z-scores and Merton distances to default computed using typical accounting data of today to the same risk measures computed under a hypothetical future blockchain regime.
Keywords: G33; G39; M41; M42; 330; blockchain; credit risk modeling; real-time accounting